The History, Present and Future of Allergen Standardization in the United States and Europe - Zimmer, Julia; Bridgewater, Jennifer; Ferreira, Fatima; van Ree, Ronald; Rabin, Ronald L.; Vieths, Stefan (Frontiers in Immunology, 2021)
The topic of standardization in relation to allergen products has been discussed by allergists, regulators, and manufacturers for a long time. In contrast to synthetic medicinal products, the natural origin of allergen products makes the necessary comparability difficult to achieve. This holds true for both aspects of standardization: Batch-to-batch consistency (or product-specific standardization) and comparability among products from different manufacturers (or cross-product comparability). In this review, we focus on how the United States and the European Union have tackled the topic of allergen product standardization in the past, covering the early joint standardization efforts in the 1970s and 1980s as well as the different paths taken by the two players thereafter until today. So far, these two paths have been based on rather classical immunological methods, including the corresponding benefits like simple feasability. New technologies such as mass spectrometry present an opportunity to redefine the field of allergen standardization in the future.